Integrated university training in bioethics and information technology for dignified care - Reluz-Barturen, Francisco Felizardo (2025)
Contemporary university work cannot be understood without computer applications, and they must be used without their pedagogical use altering the essence and purpose of educating people integrally. Technology facilitates access to knowledge and communication, but inappropriate use can be harmful, which requires training in solid bioethical criteria to avoid harmful decisions that may be detrimental to the people they will serve in the future exercise of their profession. Ethics, in its various forms (metaethics, normative ethics, ethics of minimums, among others), offers frameworks to address dilemmas related to technology in university education, promoting informed and responsible decisions. Bioethics, with approaches such as personalist, principlist, virtue bioethics, ecological and pragmatic, emphasizes the importance of human dignity and environmental sustainability in the academic context. The interdisciplinary article investigates and theoretically analyzes these aspects to motivate a suitable training in the university community, from bioethics, in the responsible use of technoscience and informatics.